2014
DOI: 10.15623/ijret.2014.0325004
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Calcined Clayey Diatomite as Cement Replacement Materials: Microstructure and Pore Structure Study

Abstract: This manuscript introduces clayey diatomite from Jelšovec deposit in Slovakia intended

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Cupola furnace slag (CFS), even when very finely ground, possesses much lower pozzolanic reactivity than fly ash, or even, blast furnace slag [45]. Furthermore, [42] also found that these slags possess higher acidity, lower pozzolanicity and a highly crystalline structure.…”
Section: Cupola Furnace Slagmentioning
confidence: 99%
“…Cupola furnace slag (CFS), even when very finely ground, possesses much lower pozzolanic reactivity than fly ash, or even, blast furnace slag [45]. Furthermore, [42] also found that these slags possess higher acidity, lower pozzolanicity and a highly crystalline structure.…”
Section: Cupola Furnace Slagmentioning
confidence: 99%